(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the role of literary translation in the context of intercultural communication. It explores various functions of translation, including preserving the cultural nuances of the original text, adapting literary works for a new audience, and conveying the emotional and artistic essence of the text. The methods and strategies used by translators to convey the meaning and style of the original work, taking into account cultural and linguistic differences, are discussed.